OVERVIEW AND DEVELOPMENT OF INCLUSIVE EDUCATION IN INDONESIA - Ririn Ananda Putri (Proceeding International Seminar of Islamic Studies, 2023)
This paper aims to find out the picture and development of inclusive education in Indonesia. The method used is a qualitative research type method with a library research approach (literature study) with techniques and data analysis obtained from books, journals, articles, theses and other relevant sources. The results of this study show that Inclusion Education organized by the Indonesian government, namely the moderate Inclusion education model as a tangible manifestation of the government's affirmation that every citizen has the right to get education (education for all) including children with special needs without discriminating against other children. Inclusive schools can be done well when they know the characteristics of children with special needs so that we know what they need from what kind of guidance and what kind of facilities and infrastructure they need.